"Helmets aren't cool": Surfers' perceptions and attitudes towards protective headgear. (August 2021) - Dean, Nikolaus A; Bundon, Andrea
Studies indicate that head injuries account for a significant proportion of all surf-related injuries. Yet, despite these rates, the vast majority of surfers do not wear protective headgear. Noting both the high rate of head-related injuries and surfers' reluctance to wear protective headgear, this sociological study sought to critically explore surfers' perceptions and attitudes towards protective headgear, and specifically to explore why so few surfers wear protective headgear. To address these aims, the ethnographic techniques of participant observations and qualitative interviews were used. In total, 12 experienced surfers from the West Coast of Canada were interviewed and over 30 hours of participant observations were collected. The findings illustrate that surfers do not wear protective headgear for four main reasons: (1) due to the idea that protective headgear is uncomfortable and could hinder performance; (2) due to the perception that protective headgear is only for other surfers; (3) based on the belief that surfing is not a high-risk sport; and (4) because of aesthetic reasons and/or the appearance of protective headgear. Using the concepts of subcultural capital and edgework, the study demonstrates how larger socio (sub)cultural factors linked to risk, control, and status influence and underline the surfers' rationalizations for not wearing protective headgear.